IMPLEMENTASI DAN PERMASALAHAN MODEL CO-MANAJEMEN DALAM PENGELOLAAN SUMBERDAYA PERIKANAN - Baino Ali Imron (Faculty of Science and Technology University Ibrahimy, 2013)
The crisis in the management of fisheries resources caused by their utilization of fishery resources that are not wise (exploitative and not pay attention to aspects of sustainability) countries have shifted the paradigm of management so far has relied on the government (government-centered regulation) to a management paradigm that gives more space to the community users in the formulation and implementation of wisdom. There is a recognition that is constantly evolving and getting stronger, if a management regime that there can be effective and have legitimacy, then the community groups of users (user groups) of fisheries resources should be involved more actively in the management of these resources. This kind of management regime known as the co-management of fisheries (fisheries co-management). There are indications and evidence is strong that the implementation of co-management is an appropriate solution to the problems of excessive exploitation of fishery resources. One of the key factors of success of co-management of marine fisheries is a strong desire coupled with the capability (capabilities) that is stronger than all the parties involved (government and public) to share responsibility in managing fisheries resources wisely.